Measuring coastal absolute sea-level changes using GNSS interferometric reflectometry - Peng, Dongju (2021)
Rising sea levels pose one of the greatest threats to coastal zones. However, sea-level changes near the coast, particularly absolute sea-level changes, have been less well monitored than those in the open ocean. In this study, we aim to investigate the potential of Global Navigation Satellite Systems Interferometric Reflectometry (GNSS-IR) to measure coastal absolute sea-level changes and tie on-land (coastal GNSS) and offshore (satellite altimetry) observations into the same framework. We choose three coastal GNSS stations, one each in regions of subsidence, uplift and stable vertical land motions, to derive both relative sea levels and sea surface heights (SSH) above the satellite altimetry reference ellipsoid from 2008 to 2020. Our results show that the accuracy of daily mean sea levels from GNSS-IR is <1.5 cm compared with co-located tide-gauge records, and amplitudes of annual cycle and linear trends estimated from GNSS-IR measurements and tide-gauge data agree within uncertainty. We also find that the de-seasoned and de-trended SSH time series from GNSS-IR and collocated satellite altimetry are highly correlated and the estimated annual amplitudes and linear trends statistically agree well, indicating that GNSS-IR has the potential to monitor coastal absolute sea-level changes and provide valuable information for coastal sea-level and climate studies.